Simple and rapid two-step polymerase chain reaction for diagnosis of Pneumocystis carinii infection. - Tamburrini, E (1993)
Two amplification steps were made to detect Pneumocystis carinii DNA by polymerase chain reaction (PCR). pAZ102-E and pAZ102-H (standard PCR), pAZ102-L2 (sense), and pAZ102-E (antisense) (two-step PCR) were used as primers. The amplification products were analyzed by ethidium bromide. After the two-step PCR, ethidium bromide detected all samples positive by oligohybridization after one amplification step. Our two-step PCR is a rapid, cost-effective, and clinically suitable method for the detection of P. carinii infection.